The relationship between depression and anxiety and heart failure patients’ adherence to self-care recommendations - Jaafar MH,; Villiers-Tuthill A,; Mcgee H,; Morgan K, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Heart failure is a physically debilitating and psychologically distressing chronic condition. Although depressive disorder is a strong predictor of short-term deterioration of heart failure symptoms and mortality, only few studies have focused on habit and daily routines. The present study aimed to investigate the relationship between depression and anxiety and heart failure patients’ self-care behaviour. Interviews were completed with 161 patients at hospital outpatient clinics in Belfast and Dublin. Depression and anxiety were assessed using the Hospital Anxiety and Depression Scale (HADS). Self-care behaviour was assessed using the European Heart Failure Self-Care Behaviour Scale (EHFSCBS). ‘Probable’ clinical depression was indicated in 18%, and ‘probable’ caseness of anxiety disorder in 16% of patients. Self-care behaviour adherence varied considerably across behaviours and was higher for taking medication as prescribed (93.1%), and taking it easy if breathless (75.1%) and lower for daily self-weighing (13.6%), regular exercise (33.6%) and limiting fluid intake (38.5%). No significant relationship was found between overall reported self-care adherence and anxiety or depression. However, significant association with depression were found for five of the 12 self-care items, and also with anxiety for two of these. Our results demonstrated that mental well-being in patients with heart failure plays a significant role in the patients’ ability to adhere to self-care regimens.